Fullfoder med rundbalar - Widén, Aron (2005)
In this project two different types of TMR (total mixed ration) mixers were investigated, Keenan carts and JF carts. Two mixers of each brand were tested and evaluated. The aim of this project was to collect different characteristics which distinguished the mixers. To be able to do that the time for mixing, the time it takes to tare apart each bale, capacity final mixing result, energy requirement, and the optimal dry matter content were investigated. The final mixing result was measured with a Penn state particle separator. Excursions to farmers which use these mixers were made in order to get a broader view over the durability of the mixers. Their experiences and knowledge which they have collected by using the mixers was also collected. In this report a collection off different type of mixers which can be found on the Swedish market today are listed. The report also contains a deeper description of the of Keenan and JF mixers, including technical facts. The results show that the dry matter content is critical for the mixing capacity. If the dry matter content increases above 50 % the capacity decreases dramatically. The same pattern was observed for both brands. No difference in the final mixing result was observed between the Keenan and the JF mixer even though large differences were found between different farms. The differences were due to a miss handling of the mixer and because the recommendations from the distributor were ignored. The energy requirement was 12 % lower for the Keenan mixer. This was something that the farmers found very positive because of the fact that they can lower the RPM value of the tractor used for mixing. The owners of a JF mixer were pleased with the construction and the fact that the mixer easily was kept clean. The result also shows a compilation of the farmer's point of view. The result does not show any problem mixing a TMR with baled silage if it is done the right way. TMR is a rational and well developed way of using the resources from the farm, also the animals like it. With the help of a particle separator and increased knowledge the possibility of using TMR mixers with success rises. Before choosing mixer type, my advice is to review the results in this essay and find out today's users experience and appreciate them against each other. My conclusion is that both mixers works very well and the choice will be on the basis of what the farm needs. This project was made in cooperation with Martin Börjesson, advisor from Keenan system and Brink Sweden AB.